The queen of fats : why omega-3s were removed from the Western diet and what we can do to replace them - Allport, Susan (California studies in food and culture, 2006)
Gives an account of how we have become deficient in a nutrient that is essential for good health: the fatty acids known as omega-3s. This work tells the story of the vital fats, which are abundant in greens and fish. It provides information for various consumers who want to reduce the risk of heart disease, cancer, arthritis, and obesity.